Oncological Outcomes Following Computer-Aided Reconstructive Jaw Surgery - John M. Le; John Hofheins; Myra Rana; Jay Ponto; Anthony B. Morlandt; Yedeh P. Ying (Craniomaxillofacial Trauma & Reconstruction)
The purpose of this study was to analyze computer-aided surgical planning (CAS) and margin status following oncological reconstructive surgery of the jaws. A retrospective study was conducted on patients who underwent microvascular reconstructive surgery from 2014 to 2021. The predictor variable was the use of CAS. The primary and secondary outcomes were histopathological bone margin status, local recurrence, and disease-free survival (DFS). Covariates included demographic, operative, pathological, and clinical outcomes. Thirty-five CAS and fifty-two non-CAS subjects were included for analysis. Demographic characteristics such as age, sex, and comorbidities were comparable between the study groups, with all p-values > 0.05. For operative variables, the osteocutaneous radial forearm flap was more commonly used in the non-CAS group (34.6%) compared to the CAS group (2.9%) (p < 0.01). The mean follow-up period was shorter in the CAS group (31.9 months) than in the non-CAS group (42.6 months) (p < 0.01). CAS was not associated with margin status (p = 0.65) or local recurrence (p = 0.08). DFS was comparable between the study groups (p = 0.74). Bone margin involvement was not associated with any covariates. The use of CAS in oncological reconstructive jaw surgery was not associated with increased bone margin involvement.